KENDALA PELAKSANAAN DAN UPAYA PENANGANAN WORK FROM HOME /WFH DI BAPPEDA KABUPATEN GUNUNGKIDUL - Nugroho, Muhammad Fajar; Suswanta, Suswanta (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2020)
The Covid-19 pandemic prompted the Government to issue instructions for social distancing to cut Coronavirus infection. The social distancing policy for ASN is carried out by limiting working hours and working from home (WFH) while still paying attention to government public services' sustainability. This is a solution to break the chain of the spread of the increasingly widespread Covid-19 outbreak. However, to realize available services are maintained and can run well, it is necessary to carry out HR management in implementing WFH by considering the various obstacles faced. Furthermore, this study aims to identify the barriers and efforts to overcome them in implementing WFH during the Covid-19 emergency. The research was conducted on all 50 employees / ASN Bappeda Gunungkidul Regency. The results of this study indicate that five aspects become the main obstacles in implementing WFH, namely elements of the availability of computers and internet networks, details of the ability to master information technology, factors of HR governance regulations, parts of organizational culture, and aspects of performance appraisal. Meanwhile, efforts that can be made to improve the implementation of WFH can be carried out by implementing one man one computer, conducting IT training and employee mentoring, compiling workbook-based HR governance, work contracts, and SPIP (Government Internal Supervision System), improving culture. Progressive organizations, as well as improving work performance-based employee performance appraisals.